Outcomes of Lymph Node Dissection in Nephroureterectomy in the Treatment of Upper Tract Urothelial Carcinoma: Analysis of the ROBUUST Registry. Issue 2 (4th August 2022) - Hakimi, Kevin; Carbonara, Umberto; Djaladat, Hooman; Mehrazin, Reza; Eun, Daniel; Reese, Adam; Gonzalgo, Mark L.; Margulis, Vitaly; Uzzo, Robert G.; Porter, James; Sundaram, Chandru P.; Abdollah, Firas; et al.
Abstract : Purpose: We sought to evaluate outcomes of lymph node dissection (LND) in patients with upper tract urothelial carcinoma. Materials and Methods: We performed a multicenter retrospective analysis utilizing the ROBUUST (for RObotic surgery for Upper Tract Urothelial Cancer Study) registry for patients who did not undergo LND (pNx), LND with negative lymph nodes (pN0) and LND with positive nodes (pN+). Primary and secondary outcomes were overall survival (OS) and recurrence-free survival (RFS). Multivariable analyses evaluated predictors of outcomes and pathological node positivity. Kaplan-Meier analyses (KMAs) compared survival outcomes. Results: A total of 877 patients were analyzed (LND performed in 358 [40.8%]/pN+ in 73 [8.3%]). Median nodes obtained were 10.2 for pN+ and 9.8 for pN0. Multivariable analyses noted increasing age (OR 1.1, p <0.001), pN+ (OR 3.1, p <0.001) and pathological stage pTis/3/4 (OR 3.4, p <0.001) as predictors for all-cause mortality. Clinical high-grade tumors (OR 11.74, p=0.015) and increasing tumor size (OR 1.14, p=0.001) were predictive for lymph node positivity. KMAs for pNx, pN0 and pN+ demonstrated 2-year OS of 80%, 86% and 42% (p <0.001) and 2-year RFS of 53%, 61% and 35% (p <0.001), respectively. KMAs comparing pNx, pN0 ≥10 nodes and pN0 <10 nodes showed no significant difference in 2-year OS (82% vs 85% vs 84%, p=0.6) but elicited significantly higher 2-year RFS in the pN0 ≥10 group (60% vs 74% vs 54%, p=0.043). Conclusions: LND during nephroureterectomy in patients with positive lymph nodes provides prognostic data, but is not associated with improved OS. LND yields ≥10 in patients with clinical node negative disease were associated with improved RFS. In high-grade and large tumors, lymphadenectomy should be considered.